Investigating plagiarism practices of International Class students majoring in Mathematics and Natural Sciences (MNS) in writing scientific articles - Puji Wahyu Setiawaty; Ali Said Almatari; Cris T. Zita (Center for Humanities and Innovation Studies, 2023)
Plagiarism is a common problem that exists in writing scientific articles. This research investigates views of plagiarism practices by students majoring in Mathematics and Natural Science in writing a scientific article. This research is qualitative descriptive, which applies thematic analysis. The research instruments were observation checklists, documents, and interview guides. The research subjects were eight students majoring in Mathematics and Natural Sciences. This study showed that students plagiarize due to missed information, keeping original ideas, and time constraints. Missed information about plagiarism, such as not understanding what constitutes plagiarism or how to cite sources properly, can also lead to unintentional plagiarism. Keeping the sense of original ideas without proper paraphrasing can lead to plagiarism. Time constraints can be a significant factor leading to plagiarism. When students or researchers are pressured to complete assignments, papers, or projects within a limited timeframe, they may resort to unethical practices like plagiarism to meet deadlines. This research found that students of Mathematics and Natural Sciences found difficulties regarding the time constraint in translation and properly citing and referencing sources. For further research, conducting a similar topic with a large-scale sample for presenting quantitative research designs on students' attitudes toward plagiarism practices in Mathematics and Natural Sciences is recommended. The upcoming research also could investigate the level of papers’ similarity and then follow up through training to avoid plagiarism